Características de la Dinámica de Tres Familias Con Un Hijo (A) Diagnosticado Con Autismo (2015)
This research aims to describe the performance characteristics of three families from their interaction with a child diagnosed with autism, a theoretical course giving explanation of the topic which is defined by different positions that is family, family dynamics is performed (rules, organization, roles, decision making, etc.) and autism spectrum disorder (ASD); therefore provides academic, social and personal contribution, giving evidence to influential concepts from the systemic model, an example, the dynamics generated in families with a diagnosis such as autism.